Measurements and modelling of the elastic properties of artificial shales - Beloborodov, R.; Pervukhina, Marina; Lebedev, Maxim (2016)
Elastic properties of shales and their anisotropy are important for seismic imaging, seismic to well tie and borehole stability issues. These properties are mainly formed due to the mechanical compaction and are influenced by the various factors, namely mineral composition of initial sediment, pore fluid chemistry, stress conditions, etc. In this experimental work, we study the effects of mechanical compaction on the elastic properties of shales with aggregated clay microstructure and different concentration of silt inclusions. We found that elastic properties of clay matrix can be considered independent of the concentration of quartz inclusions when the latter is low. However, the high concentration of quartz inclusions perturbs the orientation distribution function of clay platelets that changes elastic properties of clay.